First record of Beauveria bassiana (Hyphomycetes: Moniliales) on adults of cassava lace bug Vatiga manihotae (Drake) (Hemiptera: Tingidae) in Brazil - Alves,L.F.A (2012)
Adults of Vatiga manihotae (Drake) were collected on cassava plantation (Manihotae esculenta Crantz), fécula branca variety, in Marechal Cândido Rondon, West region of Paraná state, Brazil, showing symptoms of fungi infection. Isolation and fungi identification procedures were performed. After that, Koch's postulates were used to prove the link between the fungus and insect and i noculated insects showed symptoms similar to the previously observed. Fungus was identified as Beauveria bassiana and caused the death of 14% of the insects 10 days after inoculation. This is the first record of natural occurrence of this species of fungus infecting V. manihote and further studies should be conducted to evaluated new isolates to control of this species.